Hubungan Empowering Leadership, Workplace Spirituality dengan Flourishing pada Wanita Karir - Salim, Agus (IAI Nasional Laa Roiba Bogor, 2025)
Career women in Indonesia have shown a significant increase in numbers but continue to face challenges such as a 23% wage gap compared to men, sexual harassment, and lower happiness levels. This study aims to describe flourishing among career women, defined as the highest level of mental well-being, encompassing life satisfaction, mental health, and productive behavior. One key factor supporting flourishing is Workplace spirituality, which refers to a sense of individual fulfillment derived from transcendence in the workplace. Workplace spirituality is influenced by Empowering leadership, characterized by leaders who empower employees through attentiveness, effective communication, and inspiration. Leaders who can empower their employees foster loyalty, self-confidence, and enhanced productivity, contributing to the development of Workplace spirituality and flourishing among career women.